Radiochemical Separation of 161Tb from Gd/Tb Matrix Using Ln Resin Column - Azmairit Aziz; Widya Tania Artha (Indonesian Journal of Chemistry, 2016)
Terbium-161 (161Tb) is a potential radiolanthanide due to its favorable properties for treatment small size of cancer. Preliminary study on radiochemical separation of 161Tb from Gd/Tb matrix using Ln resin column based on extraction chromatography method has been carried out. 161Tb radionuclide was produced by irradiation of natural Gd2O3 target through neutron thermal bombardment at G.A. Siwabessy Multipurpose Reactor. Fractions eluted from the column containing Gd/Tb matrix of irradiated natural Gd2O3 target were identified and quantified using a γ-rays spectrometer with HP-Ge detector coupled to a multichannel analyzer. The results show that the optimum condition on 161Tb separation from irradiated Gd2O3 target with radionuclide purity 99.27 ± 0.30% was obtained using HNO3 solution with concentration of 0.8 and 3 N to separate gadolinium and terbium isotope, respectively. The yield of 161Tb obtained from the separation was 61.21 ± 2.05% and Gd recovered was 97.15 ± 2.23%. Based on this experiment, 161Tb has been separated from irradiated natural gadolinium oxide target with high radionuclide purity.